2023
DOI: 10.1177/13623613221146444
|View full text |Cite
|
Sign up to set email alerts
|

Parent-to-parent support among parents of children with autism: A review of the literature

Abstract: Parents of autistic children have historically reported hardships related to raising their children. However, the access to resources related to the childrearing of an autistic child is not equitable, therefore resulting in exacerbated difficulties for parents in low-resource settings. In these situations, peer support may be a protective factor for parental resilience in which they receive various supports from other parents of an autistic child with similar experiences. Despite its potential utility, little … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
(114 reference statements)
0
1
0
Order By: Relevance
“…The findings of this study will inform the cultural adaptation of PTA to be piloted in Paraguay, which is the next step in the iterative process of cultural adaptation. Additionally, the findings of this study indicate that caregivers may benefit from programs that incorporate systems of peer support or mentoring relationships among caregivers, which may be especially a good model for low‐resourced communities (Lee et al., 2024).…”
Section: Discussionmentioning
confidence: 92%
“…The findings of this study will inform the cultural adaptation of PTA to be piloted in Paraguay, which is the next step in the iterative process of cultural adaptation. Additionally, the findings of this study indicate that caregivers may benefit from programs that incorporate systems of peer support or mentoring relationships among caregivers, which may be especially a good model for low‐resourced communities (Lee et al., 2024).…”
Section: Discussionmentioning
confidence: 92%
“…The exclusion of parents and caregivers from vocational services and the lack of mental health support for this population may also be costly for the family unit because these individuals experience higher levels of depression, anxiety, and exhaustion compared to parents of neurotypical children [25]. A promising area of practice that combats the stress and isolation felt by caregivers is parent-to-parent support such as parent mentor programs [20,26]. These programs can build robust social support systems which have been associated with lower psychological distress as well as higher positive affect for parents of autistic individuals [27].…”
Section: Inclusion Of Families In Employment Servicesmentioning
confidence: 99%
“…Additionally, the idea of parents supporting one another emphasizes the need for a collective effort to create a supportive and understanding environment for families of children with autism. Studies have shown that parent-to-parent supports are a good source of emotional support, advocacy, and knowledge related to their child's diagnosis, and practical advice (Lee et al, 2023). Some parents featured in these articles have initiated the creation of their own non-governmental organizations (NGO) for assisting parents of children with autism.…”
Section: Support/assistancementioning
confidence: 99%